Reframing Adolescent Development: Identifying Communications Challenges and Opportunities. (8th November 2021) - Busso, Daniel S.; Pool, Andrew C.; Kendall‐Taylor, Nathaniel; Ginsburg, Kenneth R.
Abstract : Understanding Americans' deeply held and widely shared assumptions about adolescents and their development can reveal key opportunities and challenges for developmental science communicators. Twenty‐nine in‐depth interviews were conducted with adolescents and adults about adolescence. We analyzed the cultural models the public use to make meaning about what adolescence is, what development involves, what adolescents need, and how adolescents can be supported. The analysis revealed several cultural models that may impede public engagement around youth issues. These dominant ways of thinking include a strong focus on the vulnerability of adolescence and a narrow understanding of how environments affect adolescent development. The findings have important implications for communicators seeking to expand and deepen public thinking about adolescence.